2018
DOI: 10.1002/adma.201707455
|View full text |Cite
|
Sign up to set email alerts
|

Anelastic and Electromechanical Properties of Doped and Reduced Ceria

Abstract: Room-temperature mechanical properties of thin films and ceramics of doped and undoped ceria are reviewed with an emphasis on the anelastic behavior of the material. Notably, the unrelaxed Young's modulus of Gd-doped ceria ceramics measured by ultrasonic pulse-echo techniques is >200 GPa, while the relaxed biaxial modulus, calculated from the stress/strain ratio of thin films, is ≈10 times smaller. Oxygen-deficient ceria exhibits a number of anelastic effects, such as hysteresis of the lattice parameter, strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 84 publications
1
29
0
Order By: Relevance
“…In these solid solutions, separately addressing the local environment around cerium and around the aliovalent dopant atoms is essential for understanding the macroscopic defect-related properties such as ionic conductivity, 3,134 electrostriction and anelasticity. 135 However, the absorption edges of different elements may be too close to each other so that their EXAFS spectra overlap, complicating analyses of both edges. Therefore, to take full advantage of the information contained in an EXAFS spectrum, the absorption edge (L I , L II or L III ) of Ce and Do must be chosen with care in order to separate them as much as possible.…”
Section: Local Structure Of Ceria Solid Solutions As Characterized Bymentioning
confidence: 99%
See 3 more Smart Citations
“…In these solid solutions, separately addressing the local environment around cerium and around the aliovalent dopant atoms is essential for understanding the macroscopic defect-related properties such as ionic conductivity, 3,134 electrostriction and anelasticity. 135 However, the absorption edges of different elements may be too close to each other so that their EXAFS spectra overlap, complicating analyses of both edges. Therefore, to take full advantage of the information contained in an EXAFS spectrum, the absorption edge (L I , L II or L III ) of Ce and Do must be chosen with care in order to separate them as much as possible.…”
Section: Local Structure Of Ceria Solid Solutions As Characterized Bymentioning
confidence: 99%
“…15. Material properties reported in ceria in recent years, such as electrostriction and anelastic behavior 135 demonstrated that local strain fields may be active under applied anisotropic stress or electric field. As a result, advanced XANES and particularly EXAFS techniques were employed in order to observe changes in Cat-O distances in situ under an applied electric field.…”
Section: Local Structure Of Ceria Solid Solutions As Characterized Bymentioning
confidence: 99%
See 2 more Smart Citations
“…In sum, the influence of strain to the oxygen diffusion in the CeO 2 coatings can be neglected, but grain boundary diffusion has to be considered besides the bulk diffusion process in the CeO 2 grains. Also, the anelastic properties of ceria might have influence on the oxygen penetration and diffusion properties in the ceria film and therefore on the determined diffusion coefficient and activation energy.…”
Section: Resultsmentioning
confidence: 99%